A Study of Reinforcement Learning in a New Multiagent Domain - Min, Hua-Qing; Zeng, Jia-An; Chen, Jian; Zhu, Jin-Hui (Proceedings of the 2008 IEEE/WIC/ACM International Conference on Web Intelligence and Intelligent Agent Technology - Volume 02, 2008)
RoboCup Keepaway is one of the most challenging multiagent systems (MAS) where a team of keepers tries to keep the ball away from the team of takers. Most of current works concentrate on the learning of keeper, not the learning of taker, which is also a great challenge to the application of reinforcement learning (RL). In this paper, we propose a task named takeaway for takers and study the learning of them. We employ an initial learning algorithm called Update on Steps (UoS) for takers and demonstrate that this algorithm has two main faults including action oscillation and reliance on designer's experience. Thereafter we present a novel RL algorithm called Dynamic CMAC Advantage Learning (DCMAC-AL). It makes use of advantage ($λ$) learning to calculate value function as well as CMAC to generalize state space, and creates novel features based on Bellman error to improve the precision of CMAC. Empirical results show that takers with DCMAC-AL can learn efficiently.